JUPITER Study Continues to Make News - Jacobson, Anne (MD Conference Express, 2009)
This article presents findings from another prespecified analysis of the JUPITER data, assessing the effect of rosuvastatin on symptomatic venous thromboembolism (VTE), which occurred about as often as myocardial infarction or stroke in the JUPITER study. Compared with placebo, rosuvastatin was associated with a 43% reduction (HR, 0.57; 95% CI, 0.37 to 0.86; p=0.007) in risk of VTE and no increase in bleeding [Glynn RJ et al. N Engl J Med 2009].